Thailand logistics trend: Logistics performance index - Alonggot Limcharoen (2018)
© Research India Publications. Thailand economy is attractive and growing strong. Whilst logistics is key driving for any country competitiveness, Thailand logistics trend shows limitation. Focusing on World Bank’s Logistics Performance Index, dated back to 2007, Thailand’s logistics has not improved. The paper explores logistics performance trend together with GDP per capita of year 2007, 2010, 2012, 2014 and 2016. The discussion includes Thailand development status on 6 logistics performance, i.e., customs, infrastructure, international shipments, logistics quality and competence, tracking and tracing and timeliness. The findings indicate that Thailand logistics needs attention if to be compete or collaborate with the world. Attentions areas included infrastructure, logistics quality and competence and tracking and tracing.